The Effectiveness of Giving Rewards in Increasing Students' Learning Motivation - Irsawinda Nadhifa; Fitri Yulianti; Fittra Tulaila (Causalita, 2024)
Education is a process where students and teachers are involved in teaching and learning activities. Motivation to learn is important for students to achieve educational goals. To maintain this motivation, intervention or strategies are needed by educators. One of the intervention methods to increase learning motivation is by giving rewards. This study aims to understand the impact of giving rewards on increasing students' learning motivation. This research includes quantitative research with an experimental research design, namely pretest-posttest one group design. This study involved a sample of 25 students of SDN X Bukittinggi. The data collection method used a questionnaire or questionnaire and observation. The data analysis technique determined for this study was the paired sample t test. The results revealed that the learning motivation of fifth grade students of SDN X Bukittinggi increased after being given a reward.